Tables of moments of sample extremes of order statistics from discrete uniform distribution - Turan, A.; Calık, S.; Gurcan, M. (My University, 2013)
In this paper, moments of sample extremes of order statistics from discrete uniform distribution are given. For n up to 15, algebraic expressions for the expected values and variances of sample extremes of order statistics from discrete uniform distribution are obtained. It is shown that with the help of the sum s (k) n , one can obtain all moments for sample extremes of order statistics from a discrete uniform distribution. Furthermore, for sample size k = 20 and n =1(1)20 , numerical results calculated by using Matlab.

Makalede, kesikli düzgün dağılımdaki sıra istatistiklerin örnek ekstremlerinin momentleri verilmiştir. Kesikli düzgün dağılımdaki sıra istatistiklerin örnek ekstremlerinin beklenen değer ve varyansları için n=15’ e kadar cebirsel ifadeler bulunmuştur. s (k) n toplamı yardımıyla kesikli düzgün dağılımdaki sıra istatistiklerin örnek ekstremlerinin bütün momentlerinin bulunabileceği görülmüştür. Ayrıca, Matlab kullanılarak k = 20 ve n =1(1)20 örnek boyutu için sayısal sonuçlar hesaplanmıştır.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Order statistics; Discrete uniform distribution; Moments; Sample extremes; Sıra istatistikleri; Kesikli düzgün dağılım; Momentler; Örnek ekstremleri